Electrooxidation mechanism of non-steroidal anti-inflammatory drug piroxicam at glassy carbon electrode - Torriero, Angel Alberto Jesus (2006)
The electrochemical oxidation behavior of the anti-inflammatory drug piroxicam at the glassy carbon electrode in 10% ACN + 90% 0.2 M Britton-Robinson Buffer is presented. Cyclic voltammetry, controlled potential electrolysis and spectroscopic techniques were used to obtain information about the reaction mechanism and product identification. After exhaustive electrolysis, the extraction followed by chromatographic separation of the reaction products gave the oxidized compounds. Using UV-Vis, GC-MS, 1H and 13C NMR techniques as well as the results of our preceding electrochemical investigation, 2-{[(carboxycarbonyl)(methyl)amino]sulfonyl}benzoic acid and 2-aminopyridine were identified. To account for the formation of these products, a detailed interpretation of the mechanism of the electrooxidation of piroxicam in acidic-buffered media was presented.